PENGARUH KETELADANAN KEPALA SEKOLAH, KOMPETENSI GURU, DAN LINGKUNGAN KERJA TERHADAP KINERJA GURU SEKOLAH DASAR DI KECAMATAN PENGASIH KABUPATEN KULON PROGO (JURNAL ILMIAH TUT WURI HANDAYANI, 2013)
The research aims to determine: (1) the extent to which the influence of principal’s modelling, teacher’s competency, and work environment on the teacher’s performance, (2) the extent to which the influence of principal’s modelling on the teacher’s performance, (3) the extent to which the influence of teacher’s competency on the teacher’s performance, and (4) the extent to which the influence of work environment on the teacher’s performance. The research was conducted in Elementary school of UPTD PAUD and Primary education in Pengasih subdistrict, Kulonprogo regency. This research method is survey method with correlative approach. The population in this research was all Public Elementary School teachers in Pengasih subdistrict, Kulonprogo regency. The sample of this research was drawn by using proportional random sampling, quota sampling, simple random sampling. The sample numbering is 180 teachers. The data was collected by using questionnaires. The data were analyzed by using multiple liniear regression technique and partial correlation technique after testing the normality, linierity, and multicollinearity test. The conclusions of this research are: (1) the teacher’s elementary school performance in Pengasih subdistrict is in the categories high, which means the performance of the teachers are good, (2) the elementary school principal’s modelling in Pengasih subdistrict is in the categories high, which means that the principal’s modelling is good, (3) the elementary school teacher’s competency in Pengasih subdistrict is in the categories high, which means the competency of teachers are good, (4) the work environment of elementary school teachers in Pengasih subdistrict is in high category, which means that the working environment is good, (5) there is a positive and significant relationship between the principal’s modelling, teacher’s competency and work environment on the teacher’s performance of elementary school teachers in Pengasih subdistrict by 54.3%, Effective contribution biggest among the three predictor variables in the study is teacher’s competency that is equal to 28.52%. While the effective contribution of the work environment by 15.07%, and the effective contribution of principal’s modelling is the smallest in the amount of 10.77%.